2015
DOI: 10.1155/2015/970940
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Motilin Receptor in Various Parts of Gastrointestinal Tract in Dogs

Abstract: Objectives. The presence of motilin receptor in the GI tract of different animal species has been verified. However, the quantitation of motilin receptor expression in different regions of the GI tract remains unclear. The aim of this study was to investigate the expression of motilin receptor in the GI tract and semiquantitatively compare the expression difference in different GI regions in dogs. Methods. Antrum, duodenum, jejunum, ileum, proximal colon, middle colon, and distal colon were obtained from vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…These observations indicate that motilin can cause GI contractions via activation of enteric neurons in in vitro . Immunohistochemical and molecular biological studies indicated the presence of the MLN-Rs in the enteric plexus ( 21 ).…”
Section: Gi Motility-stimulating Actions In Mammalsmentioning
confidence: 99%
See 2 more Smart Citations
“…These observations indicate that motilin can cause GI contractions via activation of enteric neurons in in vitro . Immunohistochemical and molecular biological studies indicated the presence of the MLN-Rs in the enteric plexus ( 21 ).…”
Section: Gi Motility-stimulating Actions In Mammalsmentioning
confidence: 99%
“…Structure-function relationship studies examined contraction and binding affinities of motilin fragments indicated the presence of three distinct regions in the motilin sequence, and these regions were suggested to have different functions. An in vitro study on rabbit duodenum contractile activity and displacement of [ 125 I]-motilin binding in the rabbit antral membrane indicated that the N-terminal [1][2][3][4][5][6][7] is the minimum basic structure for binding and biological activity, the transit region [8][9] connects the N-terminal and C-terminal regions, and the C-terminal [10][11][12][13][14][15][16][17][18][19][20][21][22] forms an a-helix to stabilize the binding of the N-terminal and MLN-Rs (50,51). On the other hand, an in vivo study in which GI motility was measured in conscious dogs indicated that the N-terminal is important for eliciting biological activities and that the middle and C-terminal portions are essential for preventing from the enzyme degradation (51).…”
Section: Characterizations Of Motilin Sequence On Vertebrates Mammalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Motilin may thus be able to induce phase III of the MMC in an endocrine pathway, acting directly on the smooth muscles since the motilin receptors are present there (267). However, the substantial portion of motilin receptors occurs also in nerves (107,267). It is possible that the greater motilin receptor density, as present in the intestinal smooth muscle, unlike in nerves, may be required to induce the MMC.…”
Section: Motilinmentioning
confidence: 99%
“…The para n-embedded tissues were cut into 4-μm sections, depara nised, rehydrated, boiled in retrieval solution and washed in PBS. After blocking in normal horse serum for 30 min, the sections were incubated with rabbit anti-dog MLNR antibody (1:100; RaQualia Pharma Inc., Taketoyo, Japan) overnight at 4°C [14]. The next day, the sections were incubated with biotinylated goat anti-rabbit antibody (Sigma, St. Louis, MO, USA) and horseradish peroxidase-conjugated avidin (Sigma, Shanghai, China) for 30 min at room temperature.…”
Section: Immunostaining Of Mlnr Immunohistochemical Staining Of Mlnrmentioning
confidence: 99%